Implementasi Kurikulum Merdeka pada Mata Pelajaran Bahasa Indonesia di SMP Muhammadiyah Rappang - Nurhasna Nurhasna; Aswadi Aswadi; Rosmini Kasman; Suardi Zain (Universitas Cokroaminoto Palopo, 2024)
The Independent Curriculum was inaugurated by the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) in February 2022. It was determined that there are several things that must be prepared before learning, after that implementing independent curriculum learning, implementing learning differentiation and assessment. This research aims to determine and describe the planning, implementation and evaluation in implementing the Independent Curriculum in Indonesian language subjects at Muhammadiyah Rappang Middle School. This research uses descriptive qualitative research methods with data collection techniques, namely observation techniques, interview techniques and documentation techniques. The data analysis technique used in this research is a qualitative data analysis technique with stages of data reduction analysis, data presentation, and drawing up conclusions. The research results show that the implementation of their curriculum in terms of learning planning, learning implementation, and learning evaluation in Indonesian language subjects at Muhammadiyah Rappang Middle School has been implemented well and sustainably. However, there are still obstacles in every challenge faced by research objects in implementing Indonesian language learning based on an independent curriculum, such as limited teaching facilities, limited infrastructure and internet access for students, difficulties adapting to the different characteristics and dialects of students who are already inherent, limitations a time when learning was project-based, limited experience and references to differentiated learning models, and initial assessment paradigms that were not yet appropriate.